2006
DOI: 10.1177/0022022106286928
|View full text |Cite
|
Sign up to set email alerts
|

Nativity and Years in the Receiving Culture as Markers of Acculturation in Ethnic Enclaves

Abstract: The current study was conducted to ascertain the validity of two commonly used markers of acculturation (nativity and years in the receiving culture) in an enclave context. Relationships between these markers and a bidimensional measure of acculturation were examined in a convenience sample of Hispanic immigrant adolescents and their caregivers in Miami. Nativity was examined using adolescent-reported data; approximately half of the youth were U.S.-born and half foreignborn, but all of the caregivers were fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(149 citation statements)
references
References 25 publications
8
137
2
2
Order By: Relevance
“…The majority of the sample was second generation adolescents (Table 1). Although acculturation measures (i.e., ARSMA) and generation status are distinct, they are still highly correlated (Phinney, 2006;Schwartz et. al., 2006) As hypothesized, there were differences in sibling behaviors between neighborhoods.…”
Section: Adolescent and Neighborhood Characteristics Unexpected Resultsmentioning
confidence: 99%
“…The majority of the sample was second generation adolescents (Table 1). Although acculturation measures (i.e., ARSMA) and generation status are distinct, they are still highly correlated (Phinney, 2006;Schwartz et. al., 2006) As hypothesized, there were differences in sibling behaviors between neighborhoods.…”
Section: Adolescent and Neighborhood Characteristics Unexpected Resultsmentioning
confidence: 99%
“…However, such practices in most cases do Volume 15(1), February 2015(http://dx.doi.org/10.17576/GEMA-2015-1501 ISSN: occur in instructed target language environment. Many migrant individuals may experience the most difficulty (or unwillingness) in adopting the practices, values, and identifications of the receiving society (Schwartz et al, 2006), but this may be true in the context where the target language is taught or used as a second or a foreign language.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with Study 2's original hypothesis, general growth curve models revealed no significant change in caregivers' American identity affirmation even after account for their ethnic identity affirmation. As previously stated, given the current study was conducted in two large ethnic enclaves, it is likely caregivers can avoid ever having to learn how to speak English or having to adapt to the U.S. Culture (Schwartz, Pantin, Sullivan, Prado, & Szapocznik, 2006). Moreover, while differences across site and nationality were not detected, it is important to note that reasons behind lack of change in caregivers' American identity affirmation may vary across context and group.…”
Section: Discussionmentioning
confidence: 82%
“…Given the high levels of Hispanicism among recent immigrants, and given that ethnic identity serves a protective function in offsetting the negative effects of discrimination (Gee et al, 2007;Mossakowski, 2003), Study 2 predicted an average positive change in caregivers' ethnic affirmation. Regarding caregivers' American affirmation, for individuals who migrate as adults it may be especially difficult to identify with the receiving society (Portes & Rumbaut, 2006;Schwartz, Pantin, Sullivan, Prado, & Szapocznik, 2006;Schwartz, Unger, Zamboanga, & Szapocznik, 2010). Moreover, it is important to note the current study was conducted in two large ethnic enclaves (i.e.,…”
Section: Study 1 -Psychometric Evaluationmentioning
confidence: 99%